Comparison of survival outcomes between radio-chemotherapy and radical hysterectomy with postoperative standard therapy in patients with stage IB1 to IIA2 cervical cancer: long-term oncological outcome analysis in 37 Chinese hospitals - Ping Liu; Lihong Lin; Yanxiang Kong; Zhifeng Huo; Lin Zhu; Xiaonong Bin; Jinghe Lang; Chunlin Chen (BMC Cancer, 2020)
Abstract Background This study aimed to compare the survival outcomes of radio-chemotherapy (R-CT) and radical hysterectomy with postoperative standard therapy (RH) in stage IB1-IIA2 cervical cancer patients. Methods Based on the large amount of diagnostic and treatment cervical cancer data in China, a real-world study and 1:1 case-control matching were used to compare overall survival (OS) and disease-free survival (DFS) in cervical cancer patients. Results In this real-world study, the 5-year OS and DFS in the R-CT group (n = 8949) were lower than those in the RH group (n = 18,152). After applying the inclusion criteria, the OS and DFS in the R-CT group (n = 582) were lower than those in the RH group (n = 4308). After 1:1 case-control matching, the 5-year OS and DFS in the R-CT group (n = 535) were lower than those in the RH group (n = 535) (OS: 76.1% vs. 84.6%, p < 0.001, HR = 1.819; DFS: 75.1% vs. 81.5%, p < 0.001, HR = 1.462, respectively). Further stratification showed that for stage IB1 and IIA1 patients, the 5-year OS and DFS in the R-CT group (n = 300) were lower than those in the RH group (n = 300) (OS: 78.9% vs. 87.0%, p < 0.001, HR = 2.160; DFS: 77.0% vs. 84.9%, p < 0.001, HR = 2.053, respectively). In stage IB2 and IIA2 patients, the 5-year OS in the R-CT group (n = 235) was lower than that in the RH group (n = 235) (72.5% vs. 81.5%, p = 0.039; HR = 1.550), but no difference in the 5-year DFS was found between the two groups (72.6% vs. 76.9%, p = 0.151). Conclusions Our study found that for stage IB1-IIA2 cervical cancer patients, RH offers better overall survival and disease-free survival outcomes than R-CT, however, due to the inherent biases of retrospective study, it needs to be confirmed by randomized trials. In addition, we need to further understand the quality of life of the two treatments. Trial registration registration number: CHiCTR1800017778 ; International Clinical Trials Registry Platform Search Port, http://apps.who.int/trialsearch/. registration date: August 14, 2018.